2013
DOI: 10.3109/00498254.2013.819594
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a suitable and selective inhibitor towards aldehyde oxidase catalyzed reactions

Abstract: 1. Aldehyde oxidase (AO) is a liver cytosolic molybdoflavoprotein enzyme whose importance in drug metabolism is gaining in the recent. The objective of this work is to find a potent and selective inhibitor for AO activity using phthalazine oxidation as a marker reaction. 2. Among organic solvents tested, it was identified that methanol was not a suitable choice for AO activity even at concentrations less than 0.2% v/v. Acetonitrile and DMSO did not show any effect till 0.5% v/v but thereafter activites tend to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…In principle, coadministration of a perpetrator drug could result in observed elevations in metabolite plasma levels as a consequence of several possible mechanisms: 1) decreased metabolite clearance due to inhibition of secondary metabolism, 2) metabolic activation (stimulation of enzyme activity), 3) enzyme induction, or 4) metabolic shunting toward the uninhibited pathway (e.g., AO) when another pathway is inhibited (e.g., P450). It is unlikely that the elevated M1 levels were due to a decrease in M1 clearance in rats pretreated with ABT, as the major M1 clearance pathway in vitro was previously determined to be XO-mediated metabolism to M2 (Morrison et al, 2012); and although the activation of AO has been previously suggested (Nirogi et al, 2014), the present increased M1 formation observed in hepatic S9 fractions absent NADPH relative to NADPH-containing reactions indicate there is no contribution from an ABT-mediated cooperativity on AO. Furthermore, data from our laboratory outlining incubations of 1 with hepatocytes revealed no increase in M1 formation when ABT was present (data not shown).…”
Section: Discussionmentioning
confidence: 42%
“…In principle, coadministration of a perpetrator drug could result in observed elevations in metabolite plasma levels as a consequence of several possible mechanisms: 1) decreased metabolite clearance due to inhibition of secondary metabolism, 2) metabolic activation (stimulation of enzyme activity), 3) enzyme induction, or 4) metabolic shunting toward the uninhibited pathway (e.g., AO) when another pathway is inhibited (e.g., P450). It is unlikely that the elevated M1 levels were due to a decrease in M1 clearance in rats pretreated with ABT, as the major M1 clearance pathway in vitro was previously determined to be XO-mediated metabolism to M2 (Morrison et al, 2012); and although the activation of AO has been previously suggested (Nirogi et al, 2014), the present increased M1 formation observed in hepatic S9 fractions absent NADPH relative to NADPH-containing reactions indicate there is no contribution from an ABT-mediated cooperativity on AO. Furthermore, data from our laboratory outlining incubations of 1 with hepatocytes revealed no increase in M1 formation when ABT was present (data not shown).…”
Section: Discussionmentioning
confidence: 42%
“…A reported approach for estimating the contribution of AO compared to other routes of metabolism (fraction metabolized by AO, or f m,AO ) in hepatocytes is the use of the AO-selective inhibitor hydralazine (30 minute pre-incubation at 25 μM) (18). Employment of raloxifene or menadione as inhibitors of AO would be inappropriate in human hepatocytes due to their lack of inhibition specificity (19, 20). Alternatively, 1-aminobenzotriazole (ABT) may be used to effectively knock down CYP-mediated metabolism without inhibiting AO metabolism, or other non-CYP pathways such as UGT (30 minute pre-incubation at 1 mM).…”
Section: Aldehyde Oxidasementioning
confidence: 99%
“…The AOX activity in rat livers was determined by measuring AOX-mediated metabolites from probe substrates MTX [ 1 , 21 , 22 ], SGX523 [ 4 ], JNJ-38877605 [ 5 ], and phthalazine [ 6 8 ] in the RLCs prepared from different groups of rats. The incubation mixtures contained RLC (1.0 mg/mL), AOX substrates (50 μM MTX or phthalazine, 10 μM SGX523 or JNJ-38877605), and PBS at a final volume of 100 μL.…”
Section: Methodsmentioning
confidence: 99%
“…It plays an important role in the oxidation of aromatic azaheterocycles. The common substrates for this reaction type include methotrexate (MTX) [ 1 3 ], SGX523 [ 4 ], JNJ-38877605 [ 5 ], and phthalazine [ 6 8 ] (Fig. 1 ).…”
Section: Introductionmentioning
confidence: 99%